Press narratives of NSA domestic surveillance. Issue 2 (14th March 2020) - Martínez, Michael T.; Greig, Jamie; Luther, Catherine A.; Baker, John
ABSTRACT: The NSA's vast domestic surveillance operations have brought to the forefront the age-old debate between the need to safeguard national security through extra-constitutional actions and the desire to uphold constitutional rights. This study analyzed the narratives offered by editorials and op-ed columns in The New York Times, The Washington Post, and The Wall Street Journal to see if it reflected a press that was fulfilling a watchdog role by critiquing NSA's domestic surveillance or served as a legitimizing agent of the agency's surveillance activities. The emergent themes suggest that The New York Times and The Washington Post, fulfilling the watchdog role, think the NSA surveillance during both time periods went too far, infringing on Americans civil rights, while The Wall Street Journal, served as a legitimizing agent, championing the NSA surveillance programs and argued that giving up civil rights was a price that needed to be paid in order to combat terrorism. While taking different stances, all three publications do attempt to sustain the democratic structure, they just come at it from different points of view.